Mitigasi Risiko Rantai Pasok Berbasis House of risk di PT. Mandiri Jogja Internasional - Akbar, Muhammad Rasyid Akbar; Apsari, Ayudyah Eka (Universitas Kadiri, 2024)
PT. Mandiri Jogja Internasional, a manufacturer of leather bags, shoes and wallets, is facing challenges in supply chain and production management. However, there is a need to explore more human and environmental contributions and integrate preventive measures in holistic production management. This study aims to identify, prioritize and prevent supply chain risks. The research procedure uses the House OF Risk (HOR) model in two phases to prioritize and address risk agents based on ARP values and calculate Total Effectiveness with related calculations to determine rosk mitigation priorities. The HOR 1 study states the process of activities and risks in the supply chain of various events, such as material calculation errors, machine breakdowns, and raw material scarcity. The HOR 2 study with findings includes preventive measures, communication strategies, inventory management, production evaluation, ergonomics, supplier sourcing, and equipment maintenance. This study establishes risk priorities, designs effective countermeasures, and encourages the integration of new technologies in production risk management